An OregonGreen488-labelled d-amino acid for visualizing peptidoglycan by super-resolution STED nanoscopy. Issue 12 (25th December 2020) - Söderström, Bill; Ruda, Alessandro; Widmalm, Göran; Daley, Daniel O.
Abstract : Fluorescent d -amino acids (FDAAs) are molecular probes that are widely used for labelling the peptidoglycan layer of bacteria. When added to growing cells they are incorporated into the stem peptide by a transpeptidase reaction, allowing the timing and localization of peptidoglycan synthesis to be determined by fluorescence microscopy. Herein we describe the chemical synthesis of an OregonGreen488-labelled FDAA (OGDA). We also demonstrate that OGDA can be efficiently incorporated into the PG of Gram-positive and some Gram-negative bacteria, and imaged by super-resolution stimulated emission depletion (STED) nanoscopy at a resolution well below 100 nm.